Abnormal expression of circulating and tumor-infiltrating carcinoembryonic antigen-related cell adhesion molecule 1 in patients with glioma - Li, Jinhu; Liu, Xiaodong; Duan, Yijun; Wang, Hongqin; Su, Wen; Wang, Yazhou; Zhuang, Guotao; Fan, Yimin (Oncology letters, 2018)
Glioma, the most prevalent primary tumor of the central nervous system, is known to evade immune surveillance and escape immune attacks by inducing immunosuppression. The homophilic interactions of the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) serve a critical function in immunoregulation. In the present study, the expression levels of CEACAM1 in peripheral blood mononuclear cells and tumor-infiltrating lymphocytes (TILs) from patients with gliomas were assessed. Furthermore, associations between CEACAM1 expression and multiple clinicopathological characteristics in patients with gliomas were analyzed. The results of the present study suggested that the expression of CEACAM1 in circulating T cells was markedly increased in patients with gliomas compared with control subjects, and was further increased in TILs. Patients with high-grade gliomas [World Health Organization (WHO) grade III-IV] demonstrated a significantly increased expression of CEACAM1 on T cells compared with those with low-grade gliomas (WHO grade I-II). Furthermore, the expression of CEACAM1 on T cells was negatively correlated with the Karnofsky score and the plasma level of interferon-γ in patients with gliomas. Immunohistochemical analysis revealed that the expression levels of CEACAM1 in high-grade glioma tissues (WHO grade III-IV) were increased compared with the expression levels in the controls, and were associated with the expression of CEACAM1 in TILs. In summary, the results of the present study indicate that homophilic interactions of CEACAM1 may participate in the progression and development of gliomas through their negative regulatory effects on T cells. Thus, CEACAM1 may be a promising candidate for targeted glioma immunotherapy.